Study of the constituents of the leaves of Nerium indicum Miller (Fam. Apocynaceae) - Gregorio, Gisela P.; Santos, Rizalina B. (Quezon City: College of Pharmacy, University of the Philippines, 1980.)
The leaves of Nerium indicum Miller (Fam. Apocynaceae) was examined for glycosides and four compounds with a maximum absorbance at 222 nm, 276 nm, and 280 nm. were isolated.
Two methods used were Method I using extraction with alcohol and Method II, employing column chromatography as a means of isolating the compounds.
Analyses were done using thin layer chromatography, Rf values, and spectrophotometric method.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, March 1980.
Keywords: Oleander; Adelfa